Analisis Kompetensi Profesional Guru dalam Meningkatkan Keefektifan Belajar Selama Pembelajaran Jarak Jauh - Lubis, Rahmat Rifai; Ramli, Muhammad; Siregar, Juhriah; Panjaitan, Ratna Wati (STAI Serdang Lubuk Pakam, 2020)
This study aims to analyze the professional competence of teachers in improving the effectiveness of learning during distance learning at MTs Al-Jihad. The approach used in this research is qualitative research with descriptive methods. Data collection used by researchers is by interviewing the teacher, and documentation in the form of print out teaching materials compiled by the teacher. Then the data were analyzed through data presentation techniques and drawing conclusions. Test the validity of the data using tringulation and methods. The results of the study indicate that a teacher must be professional, professional, in this case the teacher's ability to plan learning, the learning process, and the teacher's ability to use learning media. As for the preparation of teachers at MTs Al-Jihad, namely by preparing print out material to be read and understood by students, then the learning process carried out at MTs Al-Jihad is by distance learning according to government recommendations, the teacher works on the material and uploads it on E -learningg, as for the learning media used by teachers at MTs Al-Jihad, namely utilizing internet media, in the form of what apps, e-learning, videos, and interesting pictures, because a teacher should be able to make the media as creative as possible so that students are interested in learning